2002
DOI: 10.1177/105381510202500104
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of the Infant/Toddler Sensory Profile

Abstract: We report on initial development of the Infant/Toddler Sensory Profile; a parent questionnaire assessing a child's sensory processing abilities. Parents of 401 typically developing infants and toddlers completed the 81-item questionnaire. Findings suggest that 48 of 81 items best characterized sensory processing for children 7 to 36 months of age, whereas 36 items appeared relevant for children birth to 6 months of age. Principal component analysis for 7 to 36 month olds produced an 8-component structure accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(160 citation statements)
references
References 18 publications
4
150
1
5
Order By: Relevance
“…The cohort comprises 2366 women recruited in the first trimester of pregnancy (8)(9)(10)(11)(12)(13)(14) …”
Section: Recruitmentmentioning
confidence: 99%
“…The cohort comprises 2366 women recruited in the first trimester of pregnancy (8)(9)(10)(11)(12)(13)(14) …”
Section: Recruitmentmentioning
confidence: 99%
“…First, children of women who binge drank before knowing about the pregnancy and then continued to drink at a lower level for the remainder of the pregnancy had an almost twofold increased likelihood of scoring low in sensation avoiding. Children with low scores for sensation avoiding are more likely to engage in disruptive behaviours as a coping strategy to reduce sensory input 28. Conduct problems such as these may accumulate in early childhood through exposure to stressful situations and possibly lead to problem behaviours later 41.…”
Section: Discussionmentioning
confidence: 99%
“…The Infant/Toddler Sensory Profile is a 48-item screen for sensory processing behaviours in daily experiences (ie, auditory, visual, tactile, vestibular and oral sensory processing) 28. Mothers rate the frequency of each behaviour (1 ‘almost always’ to 5 ‘almost never’), and scores are grouped to generate four quadrants: low registration (length/intensity of stimuli needed to respond), sensation seeking (level of interest and pleasure associated with sensory stimuli), sensory sensitivity (ability to notice sensory stimuli) and sensation avoiding (need to control amount/intensity of sensory stimuli).…”
Section: Methodsmentioning
confidence: 99%
“…In previous factor analyses, Dunn and colleagues (Dunn and Brown, 1997;Dunn, 1999;Brown, Tollefson, et al, 2001;Dunn and Daniels, 2001;Dunn, 2002Dunn, , 2007 found patterns that have become known as the "quadrants" in Dunn's model of sensory processing (Dunn, 1997). With teachers as informants on the School Companion, it was important to identify what patterns might emerge.…”
Section: Factor Analysismentioning
confidence: 95%